Evaluation of Tibial and Median Nerves in Patients with Diabetic Peripheral Neuropathy Using Shear Wave Elastography - Singh, Amandeep; Arora, Manik; Awal, Guneet; Sood, Mehar Kaur (Indian Journal of Radiology and Imaging, 2025)
Background Diabetes mellitus (DM) leads to diabetic peripheral neuropathy (DPN), a significant complication affecting a large percentage of diabetic patients. Traditional methods like nerve conduction studies have limitations in diagnosing DPN, especially in advanced cases. High-resolution ultrasound has emerged as a valuable tool in enhancing diagnostic accuracy.Objective The aim of the study is to evaluate the efficacy of shear wave elastography (SWE) in assessing DPN, focusing on the tibial and median nerves.Materials and Methods The study involved 100 participants categorized into groups with DPN, DM without DPN, and healthy controls. SWE was performed on the tibial and median nerves, and statistical analysis was conducted to compare the findings among the groups.Results The study found significant increases in SWE values from the normal group to the DM group, and further increases in the DPN group for both tibial and median nerves. Receiver operating characteristic analysis indicated high diagnostic accuracy of SWE in distinguishing DPN from non-DPN cases. Overall, the study suggests that SWE could be a valuable adjunctive imaging tool in diagnosing DPN, offering advantages in terms of sensitivity, specificity, and noninvasiveness.Conclusion The study concludes that SWE of the tibial and median nerves is a noninvasive, sensitive, and specific method for detecting DPN. Combining high-resolution ultrasound with SWE enhances the diagnostic accuracy of DPN.
Keywords: diabetic peripheral neuropathy; shear wave elastography; tibial nerve; median nerve